PENGARUH PROFITABILITAS, STRUKTUR KEPEMILIKAN, DAN SIZE TERHADAP NILAI PERUSAHAAN DENGAN STRUKTUR MODAL SEBAGAI VARIABEL INTERVENING PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2015 - Prilianti, Dessy; Halim, Abdul; Sari, Ati Retna (Jurnal Riset Mahasiswa Akuntansi, 2018)
This study aims to test and explain the effect of partially Return on Equity (ROE), Ownership Structure (INST), SIZE on the value of the company with a capital structure (DER) as an intervening variable on manufacturing companies listed on the Indonesia Stock Exchange (IDX). The analytical method used in this study is a quantitative method, by testing classic assumptions, and statistical analysis that is path analysis analysis. The sampling method used was purposive sampling. The variables of this study consisted of ROE, INST, SIZE as an independent variable, DER as an intervening variable, and company value as the dependent variable with a total sample of 36 manufacturing companies. Analysis results show that. ROE, INST and DER partially affect the value of the company, and INST does not affect the value of the company. For further research, it is expected to add other research variables.